1997
DOI: 10.1046/j.1365-2141.1997.1943011.x
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic leukapheresis in hyperleucocytic leukaemias: lack of correlation between degree of cytoreduction and early mortality rate

Abstract: Summary.The clinical and laboratory data of 48 leukapheresis-treated patients with hyperleucocytic leukaemia (HL) was reviewed to assess the correlation between the degree of leucoreduction and early mortality. Leukapheresis resulted in > 50% leucoreductions and postapheresis WBC counts <100 × 10 9 /l in most patients (64 . 5%). Patients presenting with neurological, respiratory or renal complications had higher early mortality rates than patients without such complications, despite similar initial WBC counts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
98
0
2

Year Published

1999
1999
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(104 citation statements)
references
References 11 publications
(13 reference statements)
4
98
0
2
Order By: Relevance
“…The efficacy of leukapheresis for patients who already present with severe complications is limited. 24,25 Porcu et al 26 suggest that cerebral infarction and/or hemorrhage are not due to sludging, but rather caused by direct endothelial damage, as a result from migration of leukemic cells into the perivascular spaces. Other measures Table 3 Overview of the rates of death other than progressive leukemia for the respective DCOG ALL and AML protocols a Protocol ALL-6 included nonhigh-risk patients only, whereas protocols ALL-7 and eight included all patients with ALL.…”
Section: Discussionmentioning
confidence: 99%
“…The efficacy of leukapheresis for patients who already present with severe complications is limited. 24,25 Porcu et al 26 suggest that cerebral infarction and/or hemorrhage are not due to sludging, but rather caused by direct endothelial damage, as a result from migration of leukemic cells into the perivascular spaces. Other measures Table 3 Overview of the rates of death other than progressive leukemia for the respective DCOG ALL and AML protocols a Protocol ALL-6 included nonhigh-risk patients only, whereas protocols ALL-7 and eight included all patients with ALL.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6][7] A study in 1997 demonstrated that 27.1% of adult patients died within 1 week of treatment. 9 Recent studies have had better survival rates; early death occurred in only 5.6% of adult patients and in 9.9% of pediatric patients. 2,20 In our study, the incidence of early death decreased dramatically in the contemporary AML protocols (22.8% vs 2.7%), although the incidence of early complications did not differ.…”
Section: -7mentioning
confidence: 99%
“…8 However, a recent study of an adult cohort failed to demonstrate that leukapheresis is associated with an improved early mortality rate. 9 To our knowledge, no recently published study has evaluated the clinical course and management of AML and hyperleukocytosis in pediatric patients. For the current study, we evaluated the medical records of 579 patients who were treated on 9 consecutive institutional AML protocols 10 and studied the clinical and biologic features of 106 pediatric patients with AML and hyperleukocytosis.…”
mentioning
confidence: 99%
“…21 Several studies have evaluated the impact on morbidity and mortality of the use of leukocytapheresis in the treatment of acute leukemias, but have yielded conflicting results. 1,17,[22][23][24][25] For example, Giles et al 22 published a retrospective study of 146 patients with newly diagnosed AML, of whom 71 underwent leukocytapheresis. Although the 2-week mortality rate was reduced in leukocytapheresis patients, there was no effect on long-term survival.…”
Section: Efficacymentioning
confidence: 99%